Analysis of Student Academic Performance to Identify New Patterns Using Linear Regression Algorithm - Adelia Putri Septiani; Akhmad Khanif Zyen; Buang Budi Wahono (Indonesian Journal of Data Science, IoT, Machine Learning and Informatics, 2025)
Abstract This research aims to analyze and identify new patterns in student academic performance using linear regression algorithms. Using data from 1001 respondents, this study analyzes the relationship between various variables such as study hours, previous scores, extracurricular activities, sleep hours, and learning practices on academic performance index. The research methodology employs a quantitative approach with linear regression analysis to identify relationships between variables. The results show significant correlations with an R-squared value of 0.783, indicating that 78.3% of the variation in performance index can be explained by the studied variables. Key findings reveal a synergistic effect between study hours and active learning practices, with performance improvements of up to 23%. The research also identifies a threshold effect on study hours above 6 hours which no longer provides significant impact. Optimal sleep patterns of 7-8 hours show positive correlation with highest academic performance. This study provides important contributions to understanding the factors influencing academic performance and can be used as a basis for developing more effective learning strategies. Keywords: academic performance, linear regression, learning patterns, educational data analysis, performance index.